Results of an Online Community Needs Assessment for Psychoeducational Interventions Among Partners of Hereditary Breast Cancer Previvors and Survivors - Tercyak, Kenneth P (Gunther Eysenbach, 2012)
BACKGROUND: Spouses and partners (“partners”) of women at-risk for (“previvors”) and surviving with hereditary breast/ovarian cancer are a primary source of support within their families. Yet, little is known about partners’ needs for psychoeducational intervention to enhance their cancer risk knowledge, coping, and support role functioning. OBJECTIVE: To determine the type and range of need for psychoeducational intervention among partners of hereditary breast cancer previving and surviving women, and to understand the potential role of the Internet and other communication channels in meeting that need. METHODS: We conducted a secondary data analysis on partners’ needs that were originally assessed via an online community-based organization devoted to hereditary breast cancer. Partners’ demographic characteristics, need for psychoeducation, and likelihood of using various communication channels were assessed along with other constructs. Analyses examined commonly-occurring clusters of likely intervention use and by communication channel. RESULTS: Partners (n =143) endorsed a moderately high level of need for psychoeducation and did so across multiple content areas (e.g., role functioning, decision making, communication, intimacy). Factor analysis identified three commonly-preferred communication channels: 1) self-help materials, 2) online interactions, and 3) interpersonal interactions. A cluster analysis among these factors identified three groups of partners based on their likelihood of psychoeducational intervention use (low [18%], moderate [55%], and high [27%] users). In a covariate-adjusted MANOVA, moderate and high intervention users reported significantly greater need for psychoeducation compared to low users (F(2,132) = 9.15, P < .001). CONCLUSIONS: A majority of assessed partners perceived a need for psychoeducational interventions surrounding hereditary breast cancer risk. Internet-based, interactive resources may be an efficient mechanism to reach large numbers of partners with tailored content. Research is warranted to inform the design and deployment of these resources to ensure quality and high impact, and ultimately to examine ways to integrate these resources into clinical care.